2010
DOI: 10.1002/cctc.201000271
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Supported Metal Cluster Catalysts: Ir4 and Ir6

Abstract: Conversion of adsorbed mononuclear metal complexes, usually organometallics, into supported clusters by treatment in reactive atmospheres * Adsorption of metal clusters stabilized with organic ligands * Deposition of size-selected ligand-free gas-phase metal clusters onto planar supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 62 publications
4
54
0
Order By: Relevance
“…Iridium complexes play important roles in oxidation (e.g., of alcohols [4][5][6], phenols [7][8][9], and amines [10,11]), hydrogenation [12,13], C-H activation [14][15][16], cycloaddition (e.g., [2 + 2 + 2] [17][18][19], [2 + 2 + 1] [20,21], and [4 + 2] [22,23]), cycloisomerization [1,2], and ring-opening reactions [24]. The richness of this chemistry explains the broad interest in the properties of the family of iridium complexes and clusters [25]. Ozin and coworkers [26][27][28] reported the synthesis of Ir(CO) n (n = 1-4) and Ir 2 (CO) 8 clusters in a matrix.…”
Section: Introductionmentioning
confidence: 98%
“…Iridium complexes play important roles in oxidation (e.g., of alcohols [4][5][6], phenols [7][8][9], and amines [10,11]), hydrogenation [12,13], C-H activation [14][15][16], cycloaddition (e.g., [2 + 2 + 2] [17][18][19], [2 + 2 + 1] [20,21], and [4 + 2] [22,23]), cycloisomerization [1,2], and ring-opening reactions [24]. The richness of this chemistry explains the broad interest in the properties of the family of iridium complexes and clusters [25]. Ozin and coworkers [26][27][28] reported the synthesis of Ir(CO) n (n = 1-4) and Ir 2 (CO) 8 clusters in a matrix.…”
Section: Introductionmentioning
confidence: 98%
“…Gates [20][21][22]. Their studies [23] bring insight into a catalytic activity of supported metal clusters and it was revealed that metal clusters bonded to oxide or zeolite supports, may combine advantages of solid catalysts with the selectivity of soluble molecular catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The ideas summarized here go beyond single-metal-atom complex catalysts; the next level of complexity is small, uniform clusters of metal atoms [20]. Although the complexity is greater, the catalyst characterization in some ways becomes more informative than for single-atom metal complexes.…”
mentioning
confidence: 99%
“…Ligands placed on neighboring metal centers in MgO-supported rhodium dimer catalysts tune the catalytic activity and selectivity for hydrogenation of 1,3-butadiene [23,24]. Work with Ir 4 and Ir 6 clusters on a zeolite included determination of the energetics of hydrogen addition as well as hydrogen spillover from the support [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation